Alfvén eigenmodes including magnetic island effects in the TJ-II stellarator. (17th August 2015) - Sun, B.J.; Ochando, M.A.; López-Bruna, D.
Abstract: Coherent modes in NBI-heated plasmas of the TJ-II stellarator at frequencies generally below those of helicity induced Alfvén eigenmodes ( ) are explained as global Alfvén eigenmodes (GAE) and discrete shear-Alfvén eigenmodes induced by a non-rotating magnetic island (MIAE). Rotating islands are also found to interact with Alfvén eigenmodes: if they share the same helicity, they disturb each other; otherwise, new Alfvén modes can be excited via wave-wave coupling.